The Effect of Question Box Assisted Talking Stick Learning Method on Student Learning Outcomes in Class III Civics Learning at Elementary School: Pengaruh Metode Pembelajaran Kotak Pertanyaan Bantuan Talking Stick Terhadap Hasil Belajar Siswa Pada Pembelajaran PKn Kelas III di SD - Ulfa Amilatun An``'nisa; Vanda Rezania (Academia Open, 2021)
The purpose of this study was to determine the effect of the Question Box-assisted Talking Stick method on Civics Class III learning at SDN Kedondong 2 Tulangan. This becomes an obstacle in the learning process, because learning is still teacher-centered so that it affects student learning outcomes. Therefore, to overcome these problems, it is necessary to change the learning methods that are usually used by teachers when teaching so that there is an increase in learning outcomes, namely through the use of the Talking Stick method with the help of the Question Box. Analysis of research data using paired sample t-test. This type of research is a pre-experimental design with data collection techniques using pre-test and post-test questions. The results showed a significant increase in results with the use of the Talking Stick method with the help of the Question Box. This can be seen from the results of the t-hit test of -21,273 and significantly 0.308, it is stated that there is an effect of the Talking Stick method with the help of Question Box on student learning outcomes.